ORANG TUA SEBAGAI UJUNG TOMBAK DALAM KESUKSESAN PENDIDIKAN KARAKTER - Bahruddin Zaini (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2021)
Family is the first environment a child experiences when born. In subsequent development the family is also the main environment in the formation of a child's personality. The early days of its growth are more spent in the family environment. So it is in the family that a child experiences the first and foremost process of education. All forms of family behavior, especially both parents, both words (oral) and deeds, both teaching, example and habits applied in family social life, will affect the pattern of development of the next child's behavior. Therefore, parents must be able to instill a good education to children from an early age, so that the development of the child's next behavior can reflect a noble personality, which benefits himself, religion, family and society and nation.